Sintesis Zeolit dari Abu Sekam Padi (OryzaSativa L.) Serta Uji Efektifitasnya Sebagai Material Antiseptik - Cinde Puspita; Dewi Rahmawati; Alhara Yuwanda (Journal of Pharmacy and Halal Studies, 2024)
Rice husks are obtained from 20% rice milling and have a silica content of 94-99% of ashed rice husks. Zeolite is a silica-based material and is known as an aluminosilicate compound, because it is formed from two main components, namely tetrahedral AlO4- and SiO4¬-. Synthetic zeolite is obtained by reacting Sodium Silicate (A) with Sodium Aluminate (B) which is then aged at 100oC for 24 hours to produce white synthetic Zeolite powder. Zeolite synthesis will be made with three variations of mixture ratios, namely 30A:70B, 50A:50B, 70A:30B and the characteristics of each will be evaluated. To test the success of this synthetic zeolite as an antiseptic material, its ability to reduce the infectious value of Bacteriuria and Candiduria will be tested, which will be represented by Escherecia coli and Candida albicans. The results obtained from the three variations of synthetic zeolite that were made had the same characteristics and had a ratio of less than two or type A. Synthetic zeolite made at a dose of 600 mg had the ability to act as an antiseptic material against Escherichia coli 104 by reducing the number of colonies to 72-79 %, as well as Candida albicans 103 was able to reduce the number of C. albicans colonies by 74-80%, this value is lower than Attapulgite 600mg in reducing the same number of colonies, namely 90% for bacteriuria and 94.90% for candiduria. To equalize its capabilities with Attapulgite 600 mg, the dosage of the synthetic zeolite obtained in the research was increased to 700 mg